2020
DOI: 10.37358/rc.20.10.8352
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Biocompatibility Evaluation of Anodic Alumina Substrates with Electrochemically Embedded Silver

Abstract: Anodic aluminum oxide films modified by silver incorporation (Al-O-Ag) under specific electrodeposition conditions were produced and their biocompatibility was analyzed by in vitro assays using mammalian cell lines. The results obtained demonstrate that Al-O-Ag substrates are well tolerated by human dermal fibroblasts. The alumina pads doped with silver for short time-period (30 seconds) showed the highest biocompatibility among all modified metal substrates and in comparison with three dental alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Figure 5 represents the obtained results. In accordance with our previous findings [27] NIH/3T3 cells demonstrated higher sensitivity to anodic alumina and silver-modified alumina substrates compared to human fibroblasts. The two specimens with anodized for 30 or 60 min alumina film showed the lowest cell survival level.…”
Section: Biocompatibility Of Silver-modified Alumina Substratessupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 5 represents the obtained results. In accordance with our previous findings [27] NIH/3T3 cells demonstrated higher sensitivity to anodic alumina and silver-modified alumina substrates compared to human fibroblasts. The two specimens with anodized for 30 or 60 min alumina film showed the lowest cell survival level.…”
Section: Biocompatibility Of Silver-modified Alumina Substratessupporting
confidence: 93%
“…It was also found that the concentration of Ag is higher at the anodic films formed in the acid electrolyte for 60 min. It is considered that cell growth, cytotoxicity, genotoxicity and biocompatibility depend on the morphological characteristics such as size, shape, surface charge, concentration, distribution of particles, exposure time and cell type [27,28]. In order to determine the concentration of deposited Ag particles into the anodized alumina layers, all samples were submitted to induction coupled plasma optical emission spectroscopy (ICP-OES) and the acquired quantitative data are graphically represented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%